Representation and Advocacy at Non-Adversary Hearings: The Need for Non-Adversary Representatives at Social Security Disability Hearings - Frank S. Bloch (Washington University Law Quarterly, 1981)
The use of independent non-adversary representatives responsible for development and presentation of all relevant evidence and issues would resolve most of the deficiencies in the hearing stage of the present Social Security process, including those resulting from deficiencies in the prehearing stages. Administrative law judges would be relieved of unmanageable responsibilities and the hearing would be conducted fairly and on a complete record without undermining the advantages of a non-adversary system or incurring the cost of instituting truly adversary proceedings.
Keywords: Administrative procedure; Legal representation; Social security; United States. Social Security Administration; United States